Current and emerging analytical techniques for geochemical and geochronological studies. (2nd November 2020) - Balaram, V.
Abstract : Progress in both basic and applied geochemical studies highly depend on the progress of the analytical instrumentation in general. In recent times, there have been spectacular developments in different instrumental analytical techniques used for accurate determinations of elemental/isotopic abundances from per cent levels to pg/g levels in a variety of geological materials. Some of the important instrumental analytical techniques which are currently in use for geochemical studies include atomic absorption spectrometry (AAS), inductively coupled plasma atomic emission spectrometry (ICP‐AES), recently introduced microwave plasma‐atomic emission spectroscopy (MP‐AES), X‐ray fluorescence spectrometry (XRF), instrumental neutron activation analysis (INAA), inductively coupled plasma mass spectrometry (ICP‐MS), ICP‐time of flight mass spectrometry (ICP‐TOF‐MS), high resolution inductively coupled plasma mass spectrometry (HR‐ICP‐MS), and multi‐collector‐ICP‐MS (MC‐ICP‐MS), with each one having its own merits and the limitations. Developments in sensitive high‐resolution ion microprobe (SHRIMP) opened up zircon geochronology and has revolutionized age dating of rocks by in‐situ isotopic analysis on single mineral grains such as zircons. Recently emerged MC‐ICP‐MS in combination with collision/reaction cell is allowing detection of small variations in natural isotopic compositions of non‐traditional stable isotopes. Advancements in other microanalytical techniques such as laser ablation‐ICP‐MS (LA‐ICP‐MS), electron probe micro‐analyser (EPMA), scanning electron microscopy and energy dispersive X‐ray spectroscopy (SEM‐EDS), laser‐induced breakdown spectroscopy (LIBS), have markedly improved direct solid analysis, in‐situ probing of individual minerals, fluids, and melt inclusions. Raman spectroscopy is currently emerging as a powerful geochemical analytical tool. Some interesting combination instruments such as ICP‐MS/AES showed synergic benefits when used in geochemical studies. There is also substantial progress in other critical areas such as sample preparation, sample decomposition, development of geochemical reference materials, and quality issues in general. Miniaturization is perhaps the most notable current trend in analytical techniques, and their use in exploration studies provide near‐real time sampling guidance in the field. In this review, all these aspects are updated, summarized and discussed at depth with practical examples. However, most of these instruments are expensive and complex and future developments may focus on some of the drawbacks of the current systems to realize their full potential for geochemical/geochronological studies. Abstract : In recent times, there have been spectacular developments in different instrumental analytical techniques such as atomic absorption spectrometry (AAS), inductively coupled plasma atomic emission spectrometry (ICP‐AES), microwave plasma‐atomic emission spectroscopy (MP‐AES), x‐ray fluorescence spectrometry (XRF), instrumental neutron activation analysis (INAA), inductively coupled plasma mass spectrometry (ICP‐MS), ICP‐time of flight mass spectrometry (ICP‐TOF‐MS), high resolution inductively coupled plasma mass spectrometry (HR‐ICP‐MS), multi‐collector‐ICP‐MS, (MC‐ICP‐MS), and sensitive high‐resolution ion microprobe (SHRIMP), which are used for accurate determinations of elemental/isotopic abundances in geological materials, for both basic and applied geochemical studies. Advancements in other microanalytical techniques such as laser ablation‐ICP‐MS (LA‐ICP‐MS), electron probe micro‐analyser (EPMA), scanning electron microscopy and energy dispersive x‐ray spectroscopy (SEM‐EDS), laser‐induced breakdown spectroscopy (LIBS), have markedly improved direct solid analysis, in‐situ probing of individual minerals, fluids, and melt inclusions. There is also substantial progress in other critical areas such as sample preparation, sample decomposition, development of geochemical reference materials, and quality issues in general.